A prospective study of maternal postnatal depressive symptoms with infant-feeding practices in a Chinese birth cohort - Tingting Sha; Xiao Gao; Cheng Chen; Ling Li; Gang Cheng; Xialing Wu; Qianling Tian; Fan Yang; Qiong He; Yan Yan (BMC, 2019)
Abstract Background The first few weeks after childbirth are critical, as women may encounter lactation problems and postpartum depression during this period. However, it is still unclear whether early breastfeeding behaviours are related to the symptoms of postnatal depression (PND) in Chinese populations. Therefore, the current study aimed to investigate the association between symptoms of PND and infant feeding practices based on a large-scale Chinese cohort. Methods A prospective study of the community-based cohort was conducted from January 2015 to December 2016. Infant feeding outcomes, including exclusive/partial breastfeeding and formula feeding, were assessed according to the WHO guidelines. Symptoms of PND were assessed by the Edinburgh Postnatal Depression Scale at 4 weeks postpartum. Multivariate generalized estimating equation models were applied to investigate the associations between depressive symptoms and infant feeding behaviours. Results A total of 956 mother-infant pairs were included. Fifty-six mothers presented screen-positive symptoms of PND with a cut-off ≥10. The percentage of early breastfeeding initiation was 75.8%, while the average duration of exclusive breastfeeding was 3.90 ± 2.33 months. Postnatal depressive symptoms were associated with a shorter breastfeeding duration (8.02 vs. 6.32 months, P < 0.05) and earlier formula introduction (4.98 vs. 3.60 months, P < 0.05). After adjustments were made for covariates, postnatal depressive symptoms were associated with an increased risk of the discontinuation of exclusive and partial breastfeeding (β = − 0.049, P = 0.047 and β = − 0.082, P = 0.006, respectively). Compared to mothers without symptoms of PND, mothers with depressive symptoms were more likely to supplement formula for their infants in the first year of life (β =0.074, P = 0.016). These associations were still significant in the sensitivity analyses, using an EPDS cut-off of ≥13. Conclusions Our findings indicate that depressive symptoms at 4 weeks postpartum are associated with the cessation of exclusive and partial breastfeeding duration and the introduction of formula in the 12 months of delivery. Early psychosocial assessment and social support should be offered to mothers in the early postpartum period to indirectly prevent adverse breastfeeding outcomes.